Development of an Automated Detection System for Nitrite in Aquatic Environments - (:unkn) unknown (My University, 2016)
The main objective of the project is to develop an automated nitrite sensor for use in aquatic environments, and more specifically for use in recirculating aquaculture systems (RAS), where monitoring can help sustain a controlled environment, protect against nitrite intoxication, and promote fish health. Detecting nitrite manually with semi-quantitative colorimetric test kits, although inexpensive and simple, is prone to inter-user variability and poor sensitivity. An automated nitrite sensor has potential to provide higher resolution measurements at both concentration and time scales and can serve as a research tool for the study of filtration systems essential in maintaining a healthy RAS environment. The questions driving the project are: How to build a device that can deliver satisfactory analytical merit (e.g., sensitivity, accuracy, precision), while maintaining reliable, inexpensive, and simple operation. The research involves investigation into detection methods and state of the art instrumentation available for nitrite, production trends in chemical total analysis systems, and centers around larger questions surrounding invention and innovation. The first steps towards such a device are benchtop prototyping of the detection and fluidic modules, their integration with wet chemistry, and the validation of the analytical process carried out by the system. The project approaches the objectives with a design that relies on commercially available components and consumables and is modular and adaptable for future possible configurations. To this end, the benchtop prototype was developed as an opto-fluidic system for automated colorimetric detection. With the exception of two custom-built PVC adaptors, the entire system was built with off-the-shelf parts for around $1,000. In addition to utilizing easily replaceable components, the system was tested using commercially available and pre-made reagents based on proven chemistry (Griess assay for nitrite). Preliminary results suggest the analytical process is capable of detecting sub-micromolar nitrite concentrations (limit of detection equal to 0.18 µM) at appreciable precision, sensitivity, and accuracy in comparison to commercial instruments.
Keywords: Aquaculture; FIA; Nitrite; Sensor